2007
DOI: 10.1038/sj.emboj.7601826
|View full text |Cite
|
Sign up to set email alerts
|

LysM domains mediate lipochitin–oligosaccharide recognition and Nfr genes extend the symbiotic host range

Abstract: Legume-Rhizobium symbiosis is an example of selective cell recognition controlled by host/non-host determinants. Individual bacterial strains have a distinct host range enabling nodulation of a limited set of legume species and vice versa. We show here that expression of Lotus japonicus Nfr1 and Nfr5 Nod-factor receptor genes in Medicago truncatula and L. filicaulis, extends their host range to include bacterial strains, Mesorhizobium loti or DZL, normally infecting L. japonicus. As a result, the symbiotic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
263
2
11

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(284 citation statements)
references
References 58 publications
8
263
2
11
Order By: Relevance
“…The perception of bacterial signaling molecules, the nodulation factors (NFs), by specific LysM-type receptor-like kinases (RLKs) in the epidermis of the host plant elicits various responses to allow root hair invasion and cell division Radutoiu et al, 2003Radutoiu et al, , 2007Jones et al, 2007;Oldroyd and Downie, 2008). While the inner cortical cells divide, outer cortical cells arrest in the G2 phase of the cell cycle, resulting in cytoplasmic bridges, the preinfection threads, through which the infection threads grow (Yang et al, 1994;van Spronsen et al, 2001).…”
mentioning
confidence: 99%
“…The perception of bacterial signaling molecules, the nodulation factors (NFs), by specific LysM-type receptor-like kinases (RLKs) in the epidermis of the host plant elicits various responses to allow root hair invasion and cell division Radutoiu et al, 2003Radutoiu et al, , 2007Jones et al, 2007;Oldroyd and Downie, 2008). While the inner cortical cells divide, outer cortical cells arrest in the G2 phase of the cell cycle, resulting in cytoplasmic bridges, the preinfection threads, through which the infection threads grow (Yang et al, 1994;van Spronsen et al, 2001).…”
mentioning
confidence: 99%
“…NFs are perceived by two receptor kinases, nodulation factor receptor1 (NFR1) and NFR5, which belong to the Lysin-motif receptor-like kinases (RLKs; Madsen et al, 2003;Radutoiu et al, 2003Radutoiu et al, , 2007. Recognition of NFs by their receptors leads to activation of the common symbiosis pathway, which is required for establishing symbiotic relationships with rhizobia and nutritionimproving mycorrhizal fungi (Kistner and Parniske, 2002;Banba et al, 2008).…”
mentioning
confidence: 99%
“…NFR1 and NFR5 are Nod factor receptors based on the observations that (1) they encode receptor-like kinases with LysM domains known to function in polysaccharide binding Radutoiu et al, 2003;Arrighi et al, 2006); (2) nfr1 and nfr5 mutants show no Nod factor responses Miwa et al, 2006a); (3) NFR1 and NFR5 bind Nod factors with high affinity (Broghammer et al, 2012); (4) the specificity of Nod factor recognition has been shown to be a function of the LysM domains of NFR5 (Bek et al, 2010); and (5) transfer of NFR1 and NFR5 to M. truncatula transferred the specificity of the L. japonicus rhizobial interaction (Radutoiu et al, 2007). The data on root hair deformation were analyzed using Student's t test, and the effects of Nod factor (compared with the no-Nod factor control) were found to be significant for both the wild type (P , 0.003) and the 59D LNP antisense line (P , 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, genetic studies implicate the LysM receptor-like kinases in specific Nod factor recognition (Radutoiu et al, 2007), and high-affinity Nod factor binding to purified NFR1 and NFR5 has been demonstrated recently (Broghammer et al, 2012). In order to better understand the function that Nod factor binding to LNP plays in the establishment of symbiotic interactions, we generated transgenic lines of Lotus japonicus that have markedly reduced LNP levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation